SLIPS OF THE TONGUE MADE BY THE ENGLISH STUDY PROGRAM STUDENTS - Tri Ayu S. Naibaho; Mazrul Aziz; Barnabas Sembiring (Universitas Bengkulu, 2018)
The purpose of this research is to identify the types of slip of the tongue made by English Education Study Program students of Bengkulu University in their proposal seminar presentation and to identify the dominant type of slip of the tongue made by English Education Study Program students of Bengkulu University in their proposal seminar presentation. The samples of this study were 5 Students English Education Study Program students of Bengkulu University who carry out seminars of each student proposal on February 23rd, 2018 and on April 27th, 2018. The instrument used in this research was the writer herself. The data were collected by using documentary method. To analyze the data, the qualitative and quantitative methods were applied. The results of this research show that there are 60 data which are taken from the proposal seminar presentation of English students. In those data there are 6 of 8 types of slip of the tongue found in students’ presentation; Anticipation, Perseveration, Exchange, Substitution, Addition and Deletion. The dominant type occurred was Substitution